2016
DOI: 10.22260/isarc2016/0019
|View full text |Cite
|
Sign up to set email alerts
|

Improving Construction Labor Productivity Using Automatic Rebar Tying Gun

Abstract: -Rebar tying is labor-intensive and expensive, with a high learning curve that restricts proficiency at the craft to a great deal of construction field experience. Obtaining this experience requires tasks that are taxing on the human body, often resulting in muscular and skeletal injuries. Previously, research and engineering controls for rebar tying/rod busting have been reasonably limited. The main contribution of this study is investigating the use of a new advanced technology to reduce the time, cost, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Productivity multipliers for construction productivity are regularly evaluated on a specially designed premise, subject to the task attributes. Safa et al (2016) studied the use of automated rebar mounting machines to improve the productivity of construction work and reduce the likelihood of accidents involving rebar yard workers. The author concluded that work is concentrated and costly, with a high learning curve that limits speciality capabilities to a lot of field involvement in construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Productivity multipliers for construction productivity are regularly evaluated on a specially designed premise, subject to the task attributes. Safa et al (2016) studied the use of automated rebar mounting machines to improve the productivity of construction work and reduce the likelihood of accidents involving rebar yard workers. The author concluded that work is concentrated and costly, with a high learning curve that limits speciality capabilities to a lot of field involvement in construction.…”
Section: Literature Reviewmentioning
confidence: 99%